Alternative resistive switching mechanism based on migration of charged counter-ions within conductive polymers - Sim, R. (2013)
In this paper, an alternative bi-stable resistive switching mechanism for non-volatile organic memory applications is reported. The memory device is formed from a sandwiched structure of Au/polyaniline:poly(4-styrenesulfonic acid) (PANI:PSSH)/ITO and operates via the migration of negatively charged counter-ions (PSS−) within the polymer composite. The electro-statically bonded PSS− within the polymer film segregates at the polymer’s interface upon electrical biasing, serving to disrupt current conduction pathways through the polymer by influencing the resonance state of the conducting main chain. By relocation of this PSS− layer at the polymer interface, electrical conductivity was modulated and an electrical bi-stable device was achieved. The resistive ratio between the ON/OFF states of the device is about 2–3 orders of magnitude, both of which can be read out for up to 500 times with negligible degradation.